Isolation and Screening of Glucoamylase I Producing Fungi from Tapioca Waste for Glucose Syrup Production in Sweet Potato (Ipomoea batatas Lenk.) and Ganyong (Canna edulis Kerr.) - INE DEWI INDRIANI (NIM 20698031), R.
Isolation and screening of glucoamylase I-producing-fungi from tapioca waste, for glucose syrup production from raw starch of sweet potato and ganyong have been carried out. The aim of this research was to obtain the best raw-starch-decomposing-fungi and glucose syrup producing fungi from tuber of sweet potato and ganyong raw starch substrate. The isolates were screened in three steps. First was to grow the fungi on sprout agar medium with the addition of 2% w/v raw starch, the second was with the addition of 5% w/v raw starch and the third was to grow the fungi in liquid medium containing basal medium with the addition of 5% raw starch. The measurements of fungal cell dry weight, glucose content, glucoamylase activity and pH have been performed every 24 hours for six days. There were 19 isolates obtained, however only 6 isolates could grow through screening. They were A, Cl, C3, P1, P5 and Y isolates. Each of six isolates was inoculated on bran substrate (koji) at pH 4,5 in the form of spore suspension. Koji extract 'which had been grown by fungi were studied using the results of SDS PAGE electrophoresis, measurements of glucoamylase and protease activities every 12 hours for four days. The productions of glucoamylase from A, Cl, C3, P1, P5 and Y isolates on bran substrate respectively were 1.984 unit/mL at the 72nd hour; 1.194 unit/mL at the 72nd hour ; 1.099 unit/mL at the 60th hour; 1.140 unit/mL at the 60th hour; 0.914 unit/mL at 60th hour, and 1.346 unit/mL at the 72nd hour. The crude enzyme extract produced by A, Cl and P1 isolates were used in decomposition process of raw starch of the sweet potato and ganyong. Following identificaton, it could be determined that A isolate was Aspergillus oryzae; CI was A. sydowi and PI isolate was A. niger. The measurements of glucose content, pH, and total acid content were performed every 12 hours for five days. The highest glucose production was achieved in sweet potato fermentation which was inoculated with crude enzyme extract of A. niger, 237.758 mg/mL at the 96th hour.